Structure and Tribomechanical Properties of Polymer Compacts Fabricated by Ultrasonic Consolidation and Compression Moulding of UHMWPE Powder; AIP Conference Proceedings; Vol. 2051 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2018 (AMHS’18) - Dvilis E. S. Edgar Sergeevich; Panin S. V. Sergey Viktorovich; Aleksenko V. O. Vladislav Olegovich; Kornienko L. A.; Buslovich D. Dmitry; Tolkachev O. S. Oleg Sergeevich; Ovechkin B. B. Boris Borisovich; Alishin T. R. (2018, 2018)
Title screen